A Feasibility study on an Herbal Antihypertensive Drug Cardiozan - Buan, Melanie C. (College of Engineering, 1999)
The rapid population growth of the country and its high poverty threshold limits the access of the population to drugs that are largely imported, thus the feasibility study on Cardiozan. Cardiozan is an herbal anti-hypertensive drug invented by Benedicto C. Cruz. It is a 250 milligram tablet made from rice bran and it normalizes blood pressure. The market study showed that the demand for anti-hypertensive drugs exceeds supply. A market share of fur percent is targeted for the product in its first year. The market for Cardiozan is determined to be the adult population with hypertension residing in the National Capital Region. Cardiozan will be marketed as an alternative drug and will be sold as the lowest-priced anti-hypertensive drug in the market at PhP 3.90 a tablet. The demand for the product can be met by employing a total of 27 people for the next five years of operation. The machine and equipment together with the workforce can produce the forecasted demand by being in operation eight hours a day and 22 days a month. The plant will require a total area of 347.75 square meters and will be located in a 786 square meter lot in Lingunan, Valenzuela Metro Manila. The total cost of the project for six months of operation is Php 22,188,887.4. Sixty percent of the total project cost will be shouldered by the investors while the remaining 40% will be financed through a loan from the Philippine National Bank. The project is financially feasible, having a net present value of Php 1,349,657.13 and a net income for the first year of Php 27,780,594.82. Also, it has the ability to pay for its debts while maintaining a high net income. It has an Internal Rate of Return of 76% which is much higher than the Minimum Attractive Rate of Return set at 25%. The payback period for the project is nine months. The organization will take the form of a corporation. A general manager will manage the affairs of the corporation and coordinate all the departments. Managers will oversee the Sales and Marketing Department, the Finance Department, the Accounting Department, the Personnel Department and the Production Department. The corporation will employ a total of 27 people for the next five years. The project cost is socially profitable based on the cost-benefit analysis done. The municipal and national government will gain from the project and the market will be provided with an alternative medicine. In conclusion, Cardiozan is assured of a potential market and it is technically feasible to meet the demand of the target market. It is financially attractive and is also socially profitable.